TAX FRAUD INTENTIONS WITH AN INTEGRATIVE MODEL APPROACH - Yenni Mangoting; Chaterine Aprilia Pangestu; Febby Melliani Tjan; Jennifer Grace Evangelina (Universitas Pendidikan Indonesia, 2021)
This study tests whether attitude, social influences, and rationalization act as the factors that influence the intention to commit tax fraud. Furthermore, this study also evaluates the influence of intention towards tax fraud behaviour and tests the moderation effect of information technology and law enforcement in the relationship between intention and tax fraud. The respondents in this study were individual taxpayers. One hundred twelve questionnaires were analyzed using the Partial Least Square (PLS) method. This study showed that attitude, social influences, and rationalization positively influence the taxpayer’s intention to commit tax fraud. Likewise, intention to commit tax fraud positively influenced taxpayers’ fraud behaviour. The moderation test result showed that compared to law enforcement, the interaction between intention and information technology is more effective to prevent tax fraud. This integrative model explains that other than anticipating fraudulent acts through tax service digitalization, morality in tax fraud needs to get more attention from tax authorities.